2015
DOI: 10.1002/we.1880
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low temperature on the mechanical properties of glass fibre–epoxy composites: static tension, compression, R = 0.1 and R =− 1 fatigue of ±45° laminates

Abstract: Effects of cold climate exposure on composite material structures are scarcely documented. As a result, even if exceptional wind conditions prevail in some cold regions, uncertainties related to composite materials durability at low temperatures may hinder development of wind energy projects in those regions. Therefore, as part of the Wind Energy Strategic Network (WESNet) of the Natural Sciences and Engineering Research Council (NSERC) of Canada, efforts were made to evaluate the effects of cold climate expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
(64 reference statements)
1
12
0
Order By: Relevance
“…A goal of the current work is thus to provide such relationships. However, because of the temperature-sensitive creep-fatigue interactions present in off-axis composites [23,30,4] -which are not accounted for in the current modelling approach -the analysis is limited to tensile fatigue along the materials main fibre orientation. Therefore, equation 2 simplifies to:…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…A goal of the current work is thus to provide such relationships. However, because of the temperature-sensitive creep-fatigue interactions present in off-axis composites [23,30,4] -which are not accounted for in the current modelling approach -the analysis is limited to tensile fatigue along the materials main fibre orientation. Therefore, equation 2 simplifies to:…”
Section: Model Descriptionmentioning
confidence: 99%
“…However, even for thermosetting matrix composites, such a simple behaviour is not always borne out by experiment. For example, R = 0.1 fatigue results by Brassard [3] for UD glass-epoxy at −40℃ and 20℃ show a statistically significant downward shift of the normalized fatigue curve at low temperature and normalized fatigue curves at -40℃ and 23℃ for ±45 • glass-epoxy at R = 0.1 obtained by Cormier et al [4] show a statistically significant change in slope parameter with temperature.…”
Section: Introductionmentioning
confidence: 97%
“…The main damage mechanism is attributed to resin softening, which results in cracks in braid yarn at elevated temperatures. Cornier et al [7] investigated the influence of low temperature on the quasi-static and fatigue behavior of glass fiber-reinforced composite. The result indicated that the compress strength and modulus were increased by 36% and 24%, respectively, when the temperature decreased from 23 C to −40 C. Youseef et al [8] studied the influence of elevated temperature on dynamic mechanical performance of E-glass composite and found that the dynamic mechanical properties are function of temperature and loading frequency.…”
Section: Introductionmentioning
confidence: 99%
“…The main damage mechanism is attributed to resin softening, which results in cracks in braid yarn at elevated temperatures. Cornier et al [ 7 ] investigated the influence of low temperature on the quasi‐static and fatigue behavior of glass fiber‐reinforced composite. The result indicated that the compress strength and modulus were increased by 36% and 24%, respectively, when the temperature decreased from 23°C to −40°C.…”
Section: Introductionmentioning
confidence: 99%
“…Significant effects of temperature and the braided angle on the compressive behaviors of 3-D braided composites were observed. 16 Cormier et al 17 researched the low-temperature effect on the static tensile, compression, and fatigue behavior of glass fiber–epoxy composites. Li et al 18 reported the temperature effect on the in-plane and out-of-plane compression behavior of 3-D multiaxial warp-knitted glass fabric/epoxy composites.…”
Section: Introductionmentioning
confidence: 99%